The Effect of Reading Interest on Learning Outcomes of the Mathematics Education Profession During the Distance Learning Period - Hali, Fitriyani (Universitas Sembilanbelas November Kolaka, 2021)
The purpose of this study was to determine the effect of reading interest on the learning outcomes of the teaching profession of students in the mathematics education study program during distance learning. This research uses a quantitative approach with a survey method. This research was conducted in the third semester of the 2020/2021 academic year during the distance learning period. This study used all students of the mathematics education study program who programmed professional education courses with a total of 25 students as the population as well as the research sample. The data collection used in the form of a Likert scale questionnaire and a test of the learning outcomes of the educational profession. The data analysis technique used descriptive and inferential analysis in the form of simple linear regression analysis. The results of data processing showed that students' reading interest reached 48% including the good category and the learning outcomes of the student education profession were also in the good category with 56% achievement. The conclusion obtained by students' reading interest has a significant effect on the learning outcomes of the educational profession in students of the mathematics education study program with a large effect of 53.9%.